2010
DOI: 10.1111/j.1365-294x.2010.04903.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of infectivity evolution in a bacteriophage

Abstract: Antagonistic coevolution between hosts and parasites is probably ubiquitous. However, very little is known of the genetic changes associated with parasite infectivity evolution during adaptation to a coevolving host. We followed the phenotypic and genetic changes in a lytic virus population (bacteriophage; phage Φ2) that coevolved with its bacterial host, Pseudomonas fluorescens SBW25. First, we show the rapid evolution of numerous unique phage infectivity phenotypes, and that both phage host range and bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
138
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(151 citation statements)
references
References 39 publications
11
138
2
Order By: Relevance
“…In single-species host-parasite interactions, parasite genotypes show differences in their host ranges and specificities on host genotypes, providing the basis for such coevolution (4)(5)(6)(7)(8). Arms race dynamics (ARD) driven by directional selection favors a broader resistance range in the host against a greater number of parasite genotypes and an increased host range in the parasite allowing more host genotypes to be infected (2,9).…”
mentioning
confidence: 99%
“…In single-species host-parasite interactions, parasite genotypes show differences in their host ranges and specificities on host genotypes, providing the basis for such coevolution (4)(5)(6)(7)(8). Arms race dynamics (ARD) driven by directional selection favors a broader resistance range in the host against a greater number of parasite genotypes and an increased host range in the parasite allowing more host genotypes to be infected (2,9).…”
mentioning
confidence: 99%
“…While there is considerable evidence for coevolutionary arms races taking place among bacteria and phages (Bohannan and Lenski 2000;Buckling and Rainey 2002a;Mizoguchi et al 2003;Brockhurst et al 2006;Forde et al 2008;Scanlan et al 2011) and various other host-parasite systems (Little et al 2006;Schulte et al 2010), there is limited evidence of fluctuations in range except for some plantfungus interactions (e.g., Thrall and Burdon 2003). Recent work with Pseudomonas fluorescens and lytic phages has shown that fluctuating selection between genotypes with similar ranges is possible, either following or in the absence of a coevolutionary arms race (Gomez and Buckling 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This means that contemporary populations may be well adapted to ancestral lineages but perform poorly against future populations (Buckling and Rainey 2002a;Mizoguchi et al 2003;Scanlan et al 2011). The fundamental principles of these "coevolutionary arms races" are captured by the gene-for-gene (GFG) framework, in which hosts can avoid infection by accumulating resistance alleles at multiple loci but parasites can counter these adaptations by gaining infectivity alleles at matching loci (Flor 1956;Sasaki 2000).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, eight viruses isolated from chemostat A on day 84 had the same RIM8.A.HR1_096 amino acid sequence, but represented five phenotypes (Table 1), indicating the role of additional mutations in other parts of the genome. Thus, host range determination in this virus appears to involve multiple genes (in addition to this candidate gene), similar to that observed in heterotrophic bacteriophage (30).…”
mentioning
confidence: 89%
“…Among the viral genomes (∼171 kb each), we identified eight nonsynonymous nucleotide substitutions in genic regions, three indels in intergenic regions, and one large deletion of several genes; one of the nucleotide substitutions was in the ϕ 9 isolate, and all of the other mutations were in the ϕ 12 isolate (Table S1). Notably, none of these changes occurred in homologs to known tail fiber genes, which are thought to be involved in determining the specificity of myoviruses (T4-like phages) (29) and have been observed to evolve in other coevolution experiments (30). Half of the nucleotide substitutions were in a 130-bp region of a 972-bp gene of unknown function (RIM8.A.HR1_096), suggesting that the region is involved in viral-host interactions.…”
mentioning
confidence: 99%